Peran Maskot Untuk Memperkuat Identitas Visual Brand - Lintang Ruhil Hidayah; Atita Sashita Rahmadiva; Shannen Shannen; Tiara Annisa Pratista (Universitas Ciputra Surabaya, 2022)
As the era develops, it has become more important for a brand to have an identity that stands out in order to survive in a world that is full of tight rivalry. Every brand has a different marketing strategy when it comes to promoting their products, one of them is by using mascots. This journal aims to explain why and how mascots have a significant role in strengthening a certain brand’s identity. By applying descriptive qualitative and quantitative research as well as literature review as the secondary data, the explanations of the mascots’ role is based on several research taken from various trusted sources that has been narrated. Hopefully, the final result of this research can be used as a basis while applying mascots for brands in order to strengthen their identity. Keywords: Brand: Brand Identity, Mascot, Role.